2015
DOI: 10.1308/003588415x14181254789484
|View full text |Cite
|
Sign up to set email alerts
|

Improving postoperative pain management in subpectoral tissue expander implant reconstruction of the breast using an elastomeric pump

Abstract: INTRODUCTION Postoperative pain after breast surgery is one of the major factors contributing to delay in mobilisation and prolonged hospital stay. A retrospective analysis was performed of patients undergoing skin sparing mastectomy and insertion of a subpectoral implant. The aim was to determine whether the use of an elastomeric local anaesthetic pump improved pain control and length of stay. METHODS Twenty-five consecutive patients undergoing the above procedure were sited with an elastomeric local anaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“… 11 The incidence of postoperative pain has increased in mastectomy patients undergoing classical reconstruction, via the subpectoral approach, with 49% experiencing acute and chronic pain. 12 15 Previously described methods to reduce postoperative pain include a pain-catheter, which can be cumbersome for patients and is associated with hypotension, pneumothorax, and infection. 16 Prepectoral breast reconstruction is associated with reconstructive outcomes comparable to those with dual-plane procedures.…”
Section: Discussionmentioning
confidence: 99%
“… 11 The incidence of postoperative pain has increased in mastectomy patients undergoing classical reconstruction, via the subpectoral approach, with 49% experiencing acute and chronic pain. 12 15 Previously described methods to reduce postoperative pain include a pain-catheter, which can be cumbersome for patients and is associated with hypotension, pneumothorax, and infection. 16 Prepectoral breast reconstruction is associated with reconstructive outcomes comparable to those with dual-plane procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the use of a Local Infusion Catheter (LIC) reduces reliance on postoperative narcotics (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Bupivacaine and ropivacaine are the two most commonly reported anesthetics used in LIC, and ropivacaine is frequently chosen over bupivacaine due to its lower cardiotoxic profile (22).…”
Section: Local Infusion Cathetermentioning
confidence: 99%
“…Bupivacaine and ropivacaine are the two most commonly reported anesthetics used in LIC, and ropivacaine is frequently chosen over bupivacaine due to its lower cardiotoxic profile (22). The LIC has been recently reported in implant-based reconstruction (40,48). Specifically, Strazisat et al reported 9.8 mg of opioid piritramide during the first 24 hours in the group that received LIC in the breast pocket, compared to 29.4 in patients who did not receive LIC.…”
Section: Local Infusion Cathetermentioning
confidence: 99%
“…18 Chaudhry et al used a portable pain pump catheter which was placed within the breast pocket and delivered bupivacaine. 19 The pain pump was removed prior to discharge and results revealed a statistically significant reduction in pain scores in addition to reduced hospital length of stay. Liposomal bupivacaine (Exparel; Pacira Pharmaceuticals, Inc.) has been approved for use in breast reconstruction and has shown positive results in alleviating postoperative pain control.…”
Section: Postoperative Pain Controlmentioning
confidence: 99%